The Influence of Cooperative Learning Think Pair Share on Critical Thinking Skill and Science Learning Outcomes Elementary School Students - Enni Siswati; Abdul Rahman; Dodi Sukmayadi (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to analyze the effect of cooperative learning think pair share on critical thinking skills and learning outcomes of fifth graders at SDN 5 Sa'dan. This research is a quantitative research with a quasi-experimental design model of the Nonequivalent Control Group Design. The population in this study were all fifth grade students of SD Negeri 5 Sadan, totaling 83 students. After randomization, VA was obtained as the experimental class and VB as the control class. Data collection techniques are through tests and observations of the process of learning activities. Based on data analysis on critical thinking skills, sig. (2-tailed) 0.000 <0.05, this shows that there is an influence of think pair share learning on students' critical thinking skills. Based on the data analysis of learning outcomes obtained the value of sig. (2-tailed) 0.000 <0.05 so it can be concluded that the cooperative learning model of think pair share type affects the learning outcomes of fifth grade students of SD Negeri 5 Sadan